2008
DOI: 10.1215/03616878-2008-024
|View full text |Cite
|
Sign up to set email alerts
|

Promoting a “Good Death”: Determinants of Pain-Management Policies in the United States

Abstract: Many Americans do not experience a good death. The inadequate treatment of pain at the end of life has been associated with a lack of supportive public policies more than a lack of evidence-based clinical practices or organizational efforts. Given a widespread lack of understanding about pain policies, we examine the critical role played by state medical boards in developing pain policies and then apply event history analysis to identify the variables most critical to the formation of these policies. We develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Providers also lack knowledge about analgesics, symptom interventions, and side effects of therapies. Still other health care system-related barriers impede pain and symptom management, such as low priority given to pain and symptom management, reimbursement and access issues, and restrictive regulation for some therapies (Berry & Dahl, 2007; Imhof & Kaskie, 2008). Some progress has been made in research to reduce some of these barriers, which have been known for nearly three decades, but others remain, especially in palliative care and end-of-life settings.…”
mentioning
confidence: 99%
“…Providers also lack knowledge about analgesics, symptom interventions, and side effects of therapies. Still other health care system-related barriers impede pain and symptom management, such as low priority given to pain and symptom management, reimbursement and access issues, and restrictive regulation for some therapies (Berry & Dahl, 2007; Imhof & Kaskie, 2008). Some progress has been made in research to reduce some of these barriers, which have been known for nearly three decades, but others remain, especially in palliative care and end-of-life settings.…”
mentioning
confidence: 99%
“…Although Nice (1984) hypothesized that more liberal states would be more likely to develop pain management policies, Imhof and Kaskie (in press) found that two of the four policies examined were not related to political ideology and the other two were more likely to be advanced in more conservative states. Given that the purpose of these particular policies was to make it more difficult for government officials to have the authority to intervene in the provision of pain management (i.e., that prescription amount alone does not determine the legitimacy of a pain prescription and that practitioners’ fears of regulatory scrutiny are addressed), it may be the case that boards in more conservative states were interested in providing up-front policies that established the parameters for limited government intervention (Brown, 1995; Hedge & Scicchitano, 1994).…”
Section: State Medical Board Policy Makingmentioning
confidence: 91%
“…It is worth mentioning that Imhof and Kaskie (in press) found that the ideology of the state governments and citizen wealth had minimal effects on medical board policy-making activity, suggesting that pain management policy adoption by medical boards remains somewhat independent from political majorities, ideological posturing, and economic cycles. As such, the boards can focus on addressing the complex, technical aspects of pain management.…”
Section: Resurrecting Advocacy Efforts To Improve End-of-life Carementioning
confidence: 97%
See 2 more Smart Citations